The need for financial and accounting outsourcing - Bezverkha, Мarina; Nikitenko, Olga (My University, 2015)
Simplifying and standardizing financial and accounting processes is a key characteristic of well-run companies, aiming to achieve a variety of good outcomes. Accounting outsourcing is one of the variants of providing the record-keeping at the enterprise for which the head of the enterprise carries the complete responsibility, in accordance with the legislation of Ukraine.
Keywords: аутсорсинг; бухгалтерський облік; accounting; outsourcing; кафедра ділової іноземної мови та міжнародної комунікації